The Association of P300 Components With Clinical Characteristics and Efficacy of Pharmacotherapy in Alcohol Use Disorder - Yuan, Jing; Wu, Changjiang; Wu, Li; Fan, Xinxin; Zeng, Tingting; Xu, Li; Wei, Yujun; Zhang, Yan; Wang, Hongxuan; Peng, Ying; Kang, Chuanyuan; Yang, Jianzhong (Frontiers in Psychiatry, 2022)
Purpose: To explore the association of P300 components with clinical characteristics and efficacy of pharmacotherapy in alcohol use disorder (AUD). Methods: 151 AUD patients and 96 healthy controls were recruited and evaluated for the symptoms of depression, anxiety, sleep and cognitive function by the Alcohol Use Disorders Identification Test (AUDIT) , the 9-item Patient Health Questionnaire (PHQ-9), the 7-item Generalized Anxiety Disorder scale (GAD-7), the Pittsburgh Sleep Quality Index (PSQI), Digit Symbol Substitution test (DSST), and event-related potential P300 which is one of averaged scalp electroencephalography responses time-locked to specific events. Among the AUD group, 101 patients finished an 8-week pharmacotherapy and were evaluated for the above data at post-intervention. Results: 1. At baseline, AUD patients had higher scores of AUDIT, PHQ-9, GAD-7, PSQI, P300 latency at Cz, Pz, Fz, and lower DSST score, smaller P300 amplitudes at Fz, Cz, Pz compared with controls. P300 components correlated significantly with alcohol dose, score of AUDIT, PHQ-9, GAD-7, PSQI, and DSST. 2. After 8 weeks’ treatment, there were significant changes for the P300 components, alcohol dose, score of AUDIT, PHQ-9, GAD-7, PSQI, DSST. Variables at baseline, including P300 amplitudes at Fz, Cz, Pz, latency of Fz, Pz, alcohol dose, scores of PHQ-9, GAD-7, PSQI and DSST, were significantly associated with changes of reduction rate of AUDIT scores. However, P300 amplitudes at Fz, Cz and Pz in AUD patients after 8-week treatment were still shorter significantly than HCs, and P300 latencies at Fz, Cz and Pz were longer significantly than HCs. 3. When validated AUC was over 0.80, the baseline variables including amplitudes at Cz, Pz, alcohol dose, and scores of PSQI could predict the changes of reduction rate of AUDIT score. Conclusion: P300 amplitudes and latencies at Fz, Cz and Pz could be used as biological markers for evaluating the clinical characters and severity of AUD. P300 amplitudes at Cz, Pz, sleep condition and cognitive function at baseline could predict the efficacy of pharmacotherapy for AUD patients.